Prior knowledge of football and memory recall - Losande, Buddy Rey L. (2003.)
This study sought to determine if high prior knowledge aboout football would yield a high score in memory recall and if a low prior knowledge about football would yield low scores in memory recall. The study also aimed to determine if high and low prior knowledge would yield high scores when paired with lecture or without a lecture. A 2 x 2 design was used to measure the interaction between high and low prior knowledge and the lecture and non-lecture conditions. (p)Thirty (30) students and thirty (30) varsity players from the University of the Philippines, Miag-ao and Central Philippine University paricipated in the study. The participants were given a 15-item questionnaire for knowledge of football and randomly assigned to the lecture and non-lecture conditions. The non-lecture group was shown a ten-minute video recording of a live football game was shown to the participants. A 5-item questionnaire derived from the short video was given. The lecture group was given a 5-minute lecture before the video was shown. To find out the significant difference in prior knowledge and lecture/non-lecture conditions, an F - test was used. (p)The results of the study showed that a high prior knowledge yielded higher scores compared to those with low prior knowledge. In the presentation of a lecture before memory tasks, it was found to have no difference in the scores attained by both high and low prior knowledge and there was no increase in their performance in memory tasks. The F - test result at 0.05 alpha level showed that there is no significant between high and low prior knowledge, the lecture and non-lecture conditions and the interaction.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Football